2017
DOI: 10.1111/jphp.12725
|View full text |Cite
|
Sign up to set email alerts
|

Drug resistance reversal by combretastatin-A4 phosphate loaded with doxorubicin in polymersomes independent of angiogenesis effect

Abstract: The findings validated the sensitization property of CA4P on DOX independent of its well-known angiogenesis effect, which would provide a novel and promising strategy for drug-resistant cancer therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The strictly controlled drug releases, which exert different mechanisms of action, might be most beneficial in terms of achieving a synergistic effect by different drugs. To date, it is known that CA-4P may sensitize drug-resistant human breast cancer MCF-7/ADR cells to DOX [135]. Additionally, Zhu et al showed that the polymersomes dual loaded with CA-4P and DOX could inhibit Pgp function by downregulating protein kinase C alpha (PKCα), stimulating ATPase activity, decrease ATP level and increase the generation of ROS, thus overcoming DOX resistance [135].…”
Section: Modifications Of the Hydroxyl Group Of Combretastatin Corementioning
confidence: 99%
“…The strictly controlled drug releases, which exert different mechanisms of action, might be most beneficial in terms of achieving a synergistic effect by different drugs. To date, it is known that CA-4P may sensitize drug-resistant human breast cancer MCF-7/ADR cells to DOX [135]. Additionally, Zhu et al showed that the polymersomes dual loaded with CA-4P and DOX could inhibit Pgp function by downregulating protein kinase C alpha (PKCα), stimulating ATPase activity, decrease ATP level and increase the generation of ROS, thus overcoming DOX resistance [135].…”
Section: Modifications Of the Hydroxyl Group Of Combretastatin Corementioning
confidence: 99%
“…Tetraethyl silicate (TEOS), triethanolamine (TEA), 5,10,15,20-tetraphenylporphyrin (TPP), (5,10,15,20)tetra(4-aminophenyl)porphyrin (NH 2 -TPP), dextran and doxorubicin hydrochloride (DOX•HCl) were all purchased from Shanghai Aladdin Biochemical Technology Co., Ltd. 3-Aminopropyltrimethoxysilane (APS) was purchased from Braunwell Chemical Technology Co., Ltd. CA4P was acquired from Solarbio Science & Technology Co., Ltd. Cetyltrimethylammonium chloride (CTAC) was purchased from Sigma-Aldrich Co., Ltd. Dulbecco's modi ed Eagle's medium (DMEM), memorial institute medium (RPMI)-1640, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT), 4',6-diamidino-2-phenylindole (DAPI), 1,3-diphenylisobenzofuran (DPBF), 2',7'-dichlorodihydro uorescein diacetate (DCFH-DA), live/dead cell viability/toxicity kit, and Annexin V-FITC/PI staining kit were all purchased from Vicmed (Xuzhou, China). Caspase 3 polyclonal antibody (caspase 3 PAb) was purchased from Proteintech Co. (USA).…”
Section: Chemical and Reagentsmentioning
confidence: 99%
“…CA4P is one of novel angiogenesis inhibitors, which can induce apoptosis by binding tubulin dimers and preventing microtubule polymerization. It's reported that CA4P has the potential to sensitize drug-resistant MCF-7/ADR cells to DOX due to the inhibition of angiogenesis [10]. Anti-angiogenesis combined with anticell proliferation has become a novel tumor therapy strategy, which was referred as "A + strategy" [11].…”
Section: Introductionmentioning
confidence: 99%
“…48 Recently, an indirect effect of inhibition of P-glycoprotein function has been suggested. 49 The experiments involved the construction of methoxy poly(ethylene glycol)-b-poly lactic acid (mPEG-b-PLA) co-polymer nano-vesicles as drug carriers. These nanoparticles were loaded with combretastatin or doxorubicin as single agents or in combination.…”
Section: Molecular Configuration and Antitumour Efficacy Of Analoguesmentioning
confidence: 99%